2012
DOI: 10.1037/a0027587
|View full text |Cite
|
Sign up to set email alerts
|

Frontal brain asymmetry in depression with comorbid anxiety: A neuropsychological investigation.

Abstract: The approach-withdrawal model posits that depression and anxiety are associated with a relative right asymmetry in frontal brain activity. Most studies have tested this model using measures of cortical brain activity such as electroencephalography. However, neuropsychological tasks that differentially employ left vs. right frontal cortical regions can also be used to test hypotheses from the model. In two independent samples (Study 1 and 2), the present study investigated the performance of currently depressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 107 publications
(165 reference statements)
2
18
0
Order By: Relevance
“…In accordance with previous evidence 5 and other studies with adults, 23,24 anxiety was significantly associated with verbal fluency performance. Our current analysis revealed that for young children this association was explained by a lower number of clusters.…”
Section: Discussionsupporting
confidence: 80%
“…In accordance with previous evidence 5 and other studies with adults, 23,24 anxiety was significantly associated with verbal fluency performance. Our current analysis revealed that for young children this association was explained by a lower number of clusters.…”
Section: Discussionsupporting
confidence: 80%
“…The present findings can be considered together with emerging differences between the two disorders in functional (Andreescu et al 2009(Andreescu et al , 2011 and structural neuroimaging (Inkster et al 2011), in neuropsychiatric and sensory testing (Bruder et al 1999;Taylor Cliff et al 2011;Nelson et al 2012) and the endocrine system (Rao et al 1989;Meller et al 1995). These Table 3.…”
Section: Discussionmentioning
confidence: 64%
“…Research on language deficits in depression has been somewhat mixed, with a number of studies indicating dysfunction (Henry & Crawford, 2005;Neu et al, 2005;O'Bryant et al, 2011;Sexton et al, 2012) but others reporting no deficits (Andersson, Lovdahl, & Malt, 2010;Nelson et al, 2012). Interestingly, several studies that have found verbal fluency dysfunction in depression relied on inpatient samples (Degl'Innocenti, Agren, Zachrisson, & Backman, 1998;Fossati, Amar, Raoux, Ergis, & Allilaire, 1999).…”
Section: Discussionmentioning
confidence: 95%